How Do Investment Banks Price Initial Public Offerings? An Empirical Analysis of Emerging Market - Abdul Rasheed (International Journal of Financial Studies, 2018)
This study investigates that how investment banks select alternative valuation models to price Initial Public Offerings (IPOs) and examine the value-relevance of each valuation model using the data of 88 IPOs listed on the Pakistan Stock Exchange (PSX) during 2000–2016. This study investigates that investment banks used Dividend Discount Model (DDM), Discounted Cash Flow (DCF) and comparable multiples valuation models on the basis of firm-specific characteristics, aggregate stock market returns and volatility before the IPOs. In this study, a binary logit regression model is used to estimate the cross-sectional determinants of the choice of valuation models by investment banks. The results reveal that underwriters are more likely to use DDM to value firms that have dividends payout trail. The investment banks select DCF when valuing the younger firms, that have more assets-in-tangible, firms that have negative sales growth and positive market returns before the IPO; while comparable multiples are used for mature firms and firms that have less assets-in-tangible. Furthermore, this study also used OLS regressions to examine the value-relevance of each valuation model and Wald-test to examine the predictive power of cross-sectional variation in the market values. The findings unveil that P/B ratio has highest but DCF has lowest predictive power to market values. The Wald-test results depict that none of the valuation methods produces an unbiased estimate of market values.